Mechanism of the Tracheal Smooth Muscle Relaxant Activity of the Cordia myxa Plant Extract in Sheep: Muhannad A. A. AlBayaty and Farid J.. AlTahan - AlBayaty, Muhannad A. A. (The Iraqi Journal of Veterinary Medicine, 2008)
Isolated tracheal smooth muscle of sheep, which is pharmacologicallyprecontracted by acetylcholine, induces relaxation when exposed to Cordiamyxa plant extract. The aim of the present study was to typify the mechanism ofCordia myxa extract induced by relaxation in the sheep trachea. 1. Cordia myxaextract relaxed both epithelium-intact and denuded sheep trachea ringscontracted by acetylcholine. The scale of relaxation on Cordia myxa extract wasdependent on the treated dose and slightly greatly in epithelium denuded ringsthan in epithelium-intact preparations. 2. L-NAME (10 nM-100 uM) but not DNAMEcompletely inhibited the relaxation in a concentration dependentmanner. 3. The Cordia myxa extract -induced relaxation was inhibited bymethylene blue (1 -100 uM), and verapamil (100 nM), and removal ofextracellular Ca2+. In contrast, Cordia myxa extract - induced relaxation waspotentiated by Nw-nitro-Larginine (L-NOARG) treatment. These results putforward that Cordia myxa extract -induced relaxation may be due to nitric oxidefrom exogenously administered L-arginine as well as endogenous nitric oxidedonors such as amino acid and arginine derivatives. Additional suggestion is thatCordia myxa extract stimulates the expression of nitric oxide synthesis, and itsactivity for nitric oxide generation is dependent on cytosolic Ca2+ originatedfrom extracellular space